2023
DOI: 10.3390/ijerph20043449
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Excessive Screen Viewing Time in Children Aged 3–15 Years and Its Effects on Physical Activity, Sleep, Eye Symptoms and Headache

Abstract: Screen viewing time is the total time spent by a child on any digital/electronic device. The objective of the present study was to determine the prevalence and predictors of excessive screen viewing time in children in Ujjain, India. This cross-sectional, community-based study was conducted through a house-to-house survey using the three-stage cluster sampling method in 36 urban wards and 36 villages of Ujjain District, India. Excessive screen viewing time was defined as screen viewing for >2 h/day. The pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 41 publications
0
0
0
Order By: Relevance
“…Excessive ST was associated with lower PA intensity levels [24] and less playing outside [5,62] in children and adolescents. Moreover, in a longitudinal study, excessive ST at 2 years of age led to less time playing outside 8 months later [48].…”
Section: Sleep and Physical Activitymentioning
confidence: 90%
See 1 more Smart Citation
“…Excessive ST was associated with lower PA intensity levels [24] and less playing outside [5,62] in children and adolescents. Moreover, in a longitudinal study, excessive ST at 2 years of age led to less time playing outside 8 months later [48].…”
Section: Sleep and Physical Activitymentioning
confidence: 90%
“…An explanation for why excessive ST leads to dry eyes and eye discomfort could be that high-concentration tasks (such as concentrating on a screen) reduce blinking rate and tear break-up time [67], causing dryness and refraction problems. Interestingly, eye pain has been identified as a PF against excessive ST [62].…”
Section: Eyesight and Headachesmentioning
confidence: 99%
“…The United States has the highest number of studies with n=7 [18], [20], [33], [38], [40], [42], [43]. India follows this with n=5 studies [15], [17], [29], [36], [41]. There are n=3 studies found in Pakistan [24], [26], [28] suggesting a growing awareness of the importance of understanding children's screen time in the country.…”
Section: Distribution Of Past Studiesmentioning
confidence: 97%
“…Meanwhile, n=6 studies used a mixed-method research design. This review indicates that the survey is the highest research approach used for collecting data on screen time behaviours with n=15 [12], [16]- [19], [22], [23], [25], [27], [30], [32], [34], [38], [40], [44], In addition, the cross-sectional study indicates n=8 studies [28], [29], [31], [23], [35], [24], [41], [26] and interviews with n=5 studies [20], [12], [23], [43], [45] respectively. Meanwhile, n=3 studies [14], [21], [37], were found to apply the longitudinal study and n=2 studies used the descriptive study [17], [36] respectively.…”
Section: Research Design Used In Past Studiesmentioning
confidence: 99%
“…[ 5 ] A study conducted in Ujjain, India, found that headaches were significantly associated with the use of mobile phones. [ 6 ] To prevent such harmful effects various guidelines have been provided by different countries.…”
Section: Introductionmentioning
confidence: 99%